International coordination and the effectiveness of aid - Arne Bigsten; Sven Tengstam (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper discusses and seeks to quantify the effects of improved donor coordination on aid effectiveness. Empirical estimates are first provided of the reductions in transaction costs that can be achieved by better donor coordination via concentration to fewer partner countries and a shift from project aid to programme-based approaches. Further estimates are presented showing how much could be gained in terms of poverty reduction by optimizing aid allocation across countries. The potential gains of a coordinated reallocation would be huge, but there are severe political implementation constraints. Still, the overall conclusion of the paper is that there are huge potential gains from donor coordination.
Keywords: F35; F55; F59; 330; donor coordination; Paris Agenda; aid efficiency; Entwicklungshilfe; Entwicklungskooperation; Allokationseffizienz